Pengaruh Literasi Keuangan, Pendapatan dan Persepsi Risiko terhadap Minat Investasi Tabungan Emas di Pegadaian: Studi pada Generasi Z di Kota Denpasar - Ni Kadek Lina Tresiana; I Putu Fery Karyada Tresiana (Hita Akuntansi dan Keuangan, 2026)
Investment refers to the allocation of financial resources with the expectation of generating returns in the future. In recent years, Generation Z has shown an increasing interest in investment activities, driven by easier access to various financial instruments. One of the investment options that has gained attention is gold savings offered by Pegadaian, which is commonly perceived as secure and practical. This study examines how financial literacy, income, and risk perception influence interest in gold savings investment among individuals belonging to Generation Z in Denpasar City. The research is conducted using a quantitative design, with primary data collected through questionnaires distributed to respondents aged 18–29 years, with a total sample of 100 individuals selected using a random sampling technique. The data were analyzed using SPSS, covering descriptive statistics, instrument testing, classical assumption tests, and multiple linear regression with hypothesis testing. The results indicate that financial literacy, income, and risk perception each have a positive and statistically significant effect on interest in gold savings investment among young investors classified as Generation Z residing in Denpasar City